Pro-Huetar Program Haiti. Contributing to a healthy diet and environmental protection through training for the implementation of agroecological practices in family, school and community gardens and farms - Centro de Gestión del Conocimiento y Cooperación Horizontal (CGCCH) (IICA, 2021)
5 pages